ANALISIS NILAI TAMBAH PUPUK ORGANIK BERBAHAN DASAR KOTORAN KAMBING PADA SANGGAR TANI MUDA DESA LANGKAK - Nur Hapiah Daulay; Yoga Nugroho (Universitas Galuh, 2023)
Sanggar Tani Muda is an institution that has been formed by the ORMAWA PPK Team of BEM FP UTU which is one of the outputs of the PPK Team. The Young Farmers Studio in Langkak village, in the livestock sub-sector, processes goat manure into organic fertilizer accompanied by the ORMAWA PPK Team, which has never calculated the added value of organic fertilizer. This study aims to determine the added value of organic fertilizers at the Young Farmers Workshop in Langkak Village, Kuala Pesisir District, Nagan Raya Regency. This research was conducted for 3 months starting from August - October 2022. The determination of respondents was carried out purposively, consisting of 1 respondent, namely the leader of the organic fertilizer business. The data collection method in this study was carried out by observation and interviews. Observation is a way of collecting data by directly observing the situation or situation in the field. The interview is the collection of data directly from the owner of the organic fertilizer business using a list of questions that have been prepared beforehand. The data analysis used is quantitative analysis, namely the added value analysis of the Hayami method. The research results show that the amount of added value of organic fertilizer obtained by the Young Farmers Studio in Langkak Village in one production process is Rp 1,500/kg.